2007
DOI: 10.1021/ol7017246
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed [3+2] Cycloaddition of Carbon Dioxide and Trimethylenemethane under Mild Conditions

Abstract: Carbon dioxide undergoes a Pd-catalyzed [3+2] cycloaddition with trimethylenemethane (TMM) under mild conditions (1 atm, 75 degrees C, 30 min) to produce a gamma-butyrolactone product in 63% yield, when the Pd-TMM complex is generated from 2-(acetoxymethyl)-3-(trimethylsilyl)propene. The reaction reported here is more rapid than the all-carbon [3+2] cycloaddition, and only the gamma-butyrolactone is produced in a competition experiment. With substituted substrates, the reaction is completely regioselective, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…A number of oxazolidine 88 and imidazolidine 89 derivatives were synthesized by [3+2] cycloaddition between oxiranes and aziridines with heterocumulenes. An extensive investigation on the palladium-catalyzed [3+2] cycloaddition reaction between 2-(acetoxymethyl)-3-(trimethylsilyl)propene 124a and carbon dioxide was reported by Greco et al 90 The reaction is presumed to proceed via the in situ generation of η 3 -Pd trimethylenemethane (TMM) complex-(A), the three atom partner, which underwent [3+2] cycloaddition with carbon dioxide to afford γ-butyro lacone 125 as the major product along with acetylated compound 126 (Scheme 40).…”
Section: [3+2] Cycloaddition Reactionsmentioning
confidence: 99%
“…A number of oxazolidine 88 and imidazolidine 89 derivatives were synthesized by [3+2] cycloaddition between oxiranes and aziridines with heterocumulenes. An extensive investigation on the palladium-catalyzed [3+2] cycloaddition reaction between 2-(acetoxymethyl)-3-(trimethylsilyl)propene 124a and carbon dioxide was reported by Greco et al 90 The reaction is presumed to proceed via the in situ generation of η 3 -Pd trimethylenemethane (TMM) complex-(A), the three atom partner, which underwent [3+2] cycloaddition with carbon dioxide to afford γ-butyro lacone 125 as the major product along with acetylated compound 126 (Scheme 40).…”
Section: [3+2] Cycloaddition Reactionsmentioning
confidence: 99%
“…2.2.2). Recently, Greco and co-workers reported that these types of compounds can be used in isolated form as the precatalysts in the carboxylation of a formal methylenecyclopropane equivalent: 2-(acetoxymethyl)-3-(trimethylsilyl)propene [161]. Thus, similarly to Inoue's report, γ-butyrolactones were obtained via a [3 + 2] cycloaddition, but under much milder reaction conditions (1 bar, 75 C, 30 min).…”
Section: Palladium-catalyzed Reactionsmentioning
confidence: 82%
“…Besides investigations on the use of other dipolarophiles such as isocyanates or carbon dioxide, new reactivities with regard to Pd‐catalyzed [3+2]‐cycloaddition reactions have been recently highlighted.…”
Section: Heterodipole/heterodipolarophile [⊖–⊕/δ⊕–δ⊖] Interactionsmentioning
confidence: 99%